Analysis of Instabilities in Electrochemical Systems Using Nonlinear Electrochemical Impedance Spectroscopy. Issue 8 (30th April 2019) - Pachimatla, Rajesh; Thomas, Merin; OC, Safeer Rahman; Srinivasan, Ramanathan
Abstract : The effect of instabilities on the nonlinear electrochemical impedance spectroscopic (NLEIS) response of a simple electron transfer reaction in a kinetic and diffusion-controlled regime was studied using classical Fe 2+ /Fe 3+ redox couple on a gold electrode. Numerical simulations were employed to calculate the NLEIS response, and the predictions were compared with experimentally acquired NLEIS data. Instabilities were introduced by continuously changing the dc potential or the active species concentrations. At high frequencies, the effect of potential instabilities manifested more clearly in higher harmonic signals than at the fundamental frequency. In case of changes in species concentrations which did not break the symmetry, the higher harmonics were not particularly more sensitive than the fundamental. An analysis of the results shows that multiple factors contribute to the higher harmonics. The sensitivity of second harmonics to the instabilities arises from the nonlinear component of the rate constant as well as the interaction between the rate constant oscillations and concentration oscillations at the applied frequency. The results show that NLEIS can be used to quickly identify instabilities which alter the symmetry.